Pathogenesis of alcoholic fatty liver a narrative review - Seitz, Helmut K.; Moreira Assunção, Bernardo; Neuman, Manuela G. (Life, 2023)
Alcohol effect hepatic lipid metabolism through various mechanisms, leading synergistically to an accumulation of fatty acids (FA) and triglycerides. Obesity, as well as dietary fat (saturated fatty acids (FA) versus poly-unsaturated fatty acids (PUFA)) may modulate the hepatic fat. Alcohol inhibits adenosine monophosphate activated kinase (AMPK). AMPK activates peroxisome proliferator activated receptor a (PPAR alpha) and leads to a decreased activation of sterol regulatory element binding protein 1c (SRABP1c). The inhibition of AMPK, and thus of PPAR alpha, results in an inhibition of FA oxidation. This ss-oxidation is further reduced due to mitochondrial damage induced through cytochrome P4502E1 (CYP2E1)-driven oxidative stress. Furthermore, the synthesis of FAs is stimulated through an activation of SHREP1. In addition, alcohol consumption leads to a reduced production of adiponectin in adipocytes due to oxidative stress and to an increased mobilization of FAs from adipose tissue and from the gut as chylomicrons. On the other side, the secretion of FAs via very-low-density lipoproteins (VLDL) from the liver is inhibited by alcohol. Alcohol also affects signal pathways such as early growth response 1 (Egr-1) associated with the expression of tumour necrosis factor alpha (TNF alpha), and the mammalian target of rapamycin (mTOR) a key regulator of autophagy. Both have influence the pathogenesis of alcoholic fatty liver. Alcohol-induced gut dysbiosis contributes to the severity of ALD by increasing the metabolism of ethanol in the gut and promoting intestinal dysfunction. Moreover, pathogen-associated molecular patterns (PAMPS) via specific Toll-like receptor (TLR) bacterial overgrowth leads to the translocation of bacteria. Endotoxins and toxic ethanol metabolites enter the enterohepatic circulation, reaching the liver and inducing the activation of the nuclear factor kappa-B (NF kappa B) pathway. Pro-inflammatory cytokines released in the process contribute to inflammation and fibrosis. In addition, cellular apoptosis is inhibited in favour of necrosis.
Gesehen am 08.04.2024